Integrated, Step-Wise, Mass-Isotopomeric Flux Analysis of the TCA Cycle - Alves, Tiago C.; Pongratz, Rebecca L.; Zhao, Xiaojian; Yarborough, Orlando; Sereda, Sam; Shirihai, Orian; Cline, Gary W.; Mason, Graeme; Kibbey, Richard G. (Cell metabolism, 2015)
Mass isotopomer multi-ordinate spectral analysis (MIMOSA) is a step-wise flux analysis platform to measure discrete glycolytic and mitochondrial metabolic rates. Importantly, direct citrate synthesis rates were obtained by deconvolving the mass spectra generated from [U-13C6]-D-glucose labeling for position-specific enrichments of mitochondrial acetyl-CoA, oxaloacetate, and citrate. Comprehensive steady-state and dynamic analyses of key metabolic rates (pyruvate dehydrogenase, β-oxidation, pyruvate carboxylase, isocitrate dehydrogenase, and PEP/pyruvate cycling) were calculated from the position-specific transfer of 13C from sequential precursors to their products. Important limitations of previous techniques were identified. In INS-1 cells, citrate synthase rates correlated with both insulin secretion and oxygen consumption. Pyruvate carboxylase rates were substantially lower than previously reported but showed the highest fold change in response to glucose stimulation. In conclusion, MIMOSA measures key metabolic rates from the precursor/product position-specific transfer of 13C-label between metabolites and has broad applicability to any glucose-oxidizing cell. [Display omitted] •LC-MS/MS positional 13C-enrichment for steady-state and dynamic flux analysis•Intersecting metabolic fluxes are disentangled by deciphering citrate isotopomers•Comprehensive precursor/product positional 13C-label transfer analysis•Quantitative mitochondrial oxidative, anaplerotic, cycling, and exchange rates Quantitative assessment of intracellular metabolism requires measuring the enzyme-to-enzyme flow of metabolites. Mitochondria have multiple nodes where metabolites intersect, scramble, and diverge, complicating isotope labeling. Alves et al. use LC-MS/MS to decipher step-wise position-specific transfer of 13C coming from glucose into subsequent metabolites through glycolysis and around the TCA cycle.